2008
DOI: 10.1002/bem.20409
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time measurement of cytosolic free calcium concentration in HL‐60 cells during static magnetic field exposure and activation by ATP

Abstract: Calcium ions are involved in a number of important signal transduction pathways in cells. Cytosolic calcium concentration ([Ca(2+)](c)) can be affected by the activation of Ca(2+) channels through the action of ligands such as ATP. The response of [Ca(2+)](c) to ligands may be affected by external factors like magnetic fields. The purpose of this study was to determine if exposure to a static magnetic field (SMF) for 800 s altered the [Ca(2+)](c) response to ATP in undifferentiated HL-60 cells. We sham exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…In contrast, some studies have found no effect of SMF exposure on calcium homeostasis. For example, in a previous study, we examined whether a 100 mT SMF would affect the [Ca 2þ ] c response to ATP [Belton et al, 2008]. Upon addition of ATP to fura 2-AM loaded HL-60 cells we observed a large and sudden increase in [Ca 2þ ] c .…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…In contrast, some studies have found no effect of SMF exposure on calcium homeostasis. For example, in a previous study, we examined whether a 100 mT SMF would affect the [Ca 2þ ] c response to ATP [Belton et al, 2008]. Upon addition of ATP to fura 2-AM loaded HL-60 cells we observed a large and sudden increase in [Ca 2þ ] c .…”
Section: Introductionmentioning
confidence: 86%
“…Cytosolic free calcium in fura-2 loaded cell samples was measured with a modified ratiometric fluorescence spectroscopy system (PTI, London, ON) comprised of a light source, chopper with filter assembly, bifurcated quartz fiber bundle, control electronics, a photomultiplier tube detector, and a personal computer [Belton et al, 2008]. The data collection and spectrometer operation were handled by commercial software (Felix32, PTI, Lawrenceville, NJ).…”
Section: Apparatus For Measurement Of Cytosolic Free Calciummentioning
confidence: 99%
See 2 more Smart Citations
“…ATP induced apoptotic cell death of both HL-60 and F-36P leukaemia cell lines [456]. Static magnetic field exposure of HL-60 cells increased the increase in [Ca 2+ ] i produced by ATP [457,458]. A 3 receptor agonists were shown to inhibit proliferation and induce apoptosis of HL-60 leukaemia cells [459,460].…”
Section: Lymphocytic Leukaemiamentioning
confidence: 98%